10-year portuguese football strategic plan: sustainable growth - Rodrigues, João Carlos de Oliveira (2022)
Analysis of main pillars in the 10-year strategic plan for Portuguese football in partnership with FPF and Deloitte. Fan engagement and how to improve their experience. Women’s football current development and how to incentivize the youth to practice. How to increase the numbers of participants, as most athletes drop the sport during university years. Which broadcasting rights model, decentralized and centralized, should be implemented in Portugal. However ,the choice remains arguable. International exposure and developing countries as an opportunity to increase viewership. This paper presents a comprehensive assessment of the strategy being created by FPF and Deloitte and makes recommendations.